Knockout of macrophage migration inhibitory factor accentuates side-stream smoke exposure-induced myocardial contractile dysfunction through dysregulated mitophagy. (July 2020) - Wang, Shuyi; Chen, Xu; Zeng, Biru; Xu, Xihui; Chen, Huaguo; Zhao, Ping; Hilaire, Michelle L.; Bucala, Richard; Zheng, Qijun; Ren, Jun
Graphical abstract: Abstract: Second hand smoke exposure increases the prevalence of chronic diseases partly attributed to inflammatory responses. Macrophage migration inhibitory factor (MIF), a proinflammatory cytokine, is involved in the pathogenesis of multiple diseases although its role in second hand smoke exposure-induced cardiac anomalies remains elusive. This study evaluated the impact of MIF knockout on side-stream smoke exposure-induced cardiac pathology and underlying mechanisms. Adult WT and MIF knockout (MIFKO) mice were placed in a chamber exposed to cigarette smoke for 1 h daily for 60 consecutive days. Echocardiographic, cardiomyocyte function and intracellular Ca 2+ handling were evaluated. Autophagy, mitophagy and apoptosis were examined using western blot. DHE staining was used to evaluate superoxide anion (O2 − ) generation. Masson trichrome staining was employed to assess interstitial fibrosis. Our data revealed that MIF knockout accentuated side-stream smoke-induced cardiac anomalies in fractional shortening, cardiomyocyte function, intracellular Ca 2+ homeostasis, myocardial ultrastructure and mitochondrial content along with overt apoptosis and O2 − generation. In addition, unfavorable effects of side-stream smoke were accompanied by excessive formation of autophagolysosome and elevated TFEB, the effect of which was exacerbated by MIF knockout. Recombinant MIF rescued smoke extract-induced myopathic anomalies through promoting AMPK activation, mitophagy and lysosomal function. Taken together, our data suggest that MIF serves as a protective factor against side-stream smoke exposure-induced myopathic changes through facilitating mitophagy and autophagolysosome formation.